2013
DOI: 10.1039/c3sc51319j
|View full text |Cite
|
Sign up to set email alerts
|

A combined experimental and quantum chemical study of CO2 adsorption in the metal–organic framework CPO-27 with different metals

Abstract: A first principles study of CO 2 adsorption is presented for a group of metal-organic frameworks (MOFs) known as CPO-27-M, where M ¼ Mg, Mn, Fe, Co, Ni, Cu, and Zn. These materials consist of onedimensional channels with a high concentration of open metal sites and have been identified as among the most promising MOFs for CO 2 capture. In addition, extensive, high-pressure, experimental adsorption results are reported for CO 2 , CH 4 , and N 2 at temperatures ranging from 278 K to 473 K. Isosteric heats of ads… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

24
206
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 180 publications
(233 citation statements)
references
References 54 publications
24
206
3
Order By: Relevance
“…35−37 The model B Figure 8. Comparison between the experimental and simulated isotherms of CO 2 inside Zn-MOF-74 at 298 K. The experimental data of Yu et al 33 and the corresponding scaled isotherm (assume only 80% of material are accessible, which is the same value we have used for Mg-MOF-74) are shown by the closed black squares and red close circle with dashed line, respectively. The symbols are the isotherms from the GCMC simulations as predicted by the different models.…”
Section: Journal Of Chemical Theory and Computationmentioning
confidence: 99%
See 1 more Smart Citation
“…35−37 The model B Figure 8. Comparison between the experimental and simulated isotherms of CO 2 inside Zn-MOF-74 at 298 K. The experimental data of Yu et al 33 and the corresponding scaled isotherm (assume only 80% of material are accessible, which is the same value we have used for Mg-MOF-74) are shown by the closed black squares and red close circle with dashed line, respectively. The symbols are the isotherms from the GCMC simulations as predicted by the different models.…”
Section: Journal Of Chemical Theory and Computationmentioning
confidence: 99%
“…Figure 8 shows that, for Zn-MOF-74, our predicted isotherm is also in good agreement with the experimentally scaled one. 33 Given that we can obtain such a good agreement by only reparameterizing the metal−guest interactions, indicating that the parameters obtained in the Mg-MOF-74 are transferable to the Zn-MOF-74 as well as the method itself.…”
Section: Journal Of Chemical Theory and Computationmentioning
confidence: 99%
“…[ 68 ] Since these studies of CO 2 adsorption in Mg 2 (dobdc), several combined experimental and theoretical approaches have been taken to identify the host-guest interactions that lead to signifi cant differences in isosteric heats among all of the metal-substituted analogs in the M 2 (dobdc) series. [ 54,69 ] Among those members, isosteric heats of adsorption ( Figure 3 ) follow a trend (Mg > Ni > Co > Fe > Mn > Zn >Cu) that unexpectedly does not correlate with the ionic radii. [ 68 ] A recent study by Yu [ 54 ] gives an explanation for the observed trend through a description of nuclear screening effects by M 2+ d-orbitals.…”
Section: Co 2 Adsorption In the M 2 (Dobdc) Seriesmentioning
confidence: 99%
“…[ 54,69 ] Among those members, isosteric heats of adsorption ( Figure 3 ) follow a trend (Mg > Ni > Co > Fe > Mn > Zn >Cu) that unexpectedly does not correlate with the ionic radii. [ 68 ] A recent study by Yu [ 54 ] gives an explanation for the observed trend through a description of nuclear screening effects by M 2+ d-orbitals. Their fi rst-principles study reveals that the relative strength of the electrostatic interaction is dictated by the effective charge of the metal cation at the open coordination site where the CO 2 binds.…”
Section: Co 2 Adsorption In the M 2 (Dobdc) Seriesmentioning
confidence: 99%
See 1 more Smart Citation